Design of Islamic Religious Education Learning Based on Digital Literacy and Moral Values - Dewi, Wini Kurnia; Ariyanti, Ira; Selamet, Selamet (Jurnal Ilmiah Profesi Pendidikan, 2026)
The development of digital technology has influenced the way students access and understand religious knowledge. In Islamic Religious Education (IRE), this condition presents challenges related to students’ digital literacy skills as well as the cultivation of attitudes and moral character in digital spaces. IRE learning still tends to focus on the delivery of content, while the integration of digital literacy and moral values has not yet been systematically designed. Therefore, an IRE learning design that is responsive to technological developments without neglecting the goal of character formation is needed. This study aims to examine and formulate a design of Islamic Religious Education learning based on digital literacy integrated with moral values. The research employs a qualitative approach through a literature study of scientific journals, books, and relevant policy documents. The data are analyzed descriptively to identify key concepts and main components in the development of an IRE learning design. The results of the study indicate that digital literacy in IRE learning should be directed toward the development of critical, ethical, and responsible competencies, not merely technological proficiency. The integration of moral values can be carried out through the selection of materials, methods, and learning activities that are contextualized with students’ digital experiences. An integrated learning design has the potential to support the achievement of IRE objectives in a manner that is more relevant to the demands of the digital era. This study is expected to contribute conceptually to the development of IRE learning and to serve as a foundation for further empirical research.